2018
DOI: 10.3390/catal8020074
|View full text |Cite
|
Sign up to set email alerts
|

g-C3N4-Based Nanomaterials for Visible Light-Driven Photocatalysis

Abstract: Graphitic carbon nitride (g-C 3 N 4 ) is a promising material for photocatalytic applications such as solar fuels production through CO 2 reduction and water splitting, and environmental remediation through the degradation of organic pollutants. This promise reflects the advantageous photophysical properties of g-C 3 N 4 nanostructures, notably high surface area, quantum efficiency, interfacial charge separation and transport, and ease of modification through either composite formation or the incorporation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
83
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 205 publications
(85 citation statements)
references
References 286 publications
1
83
0
Order By: Relevance
“…In addition, this wonder material with unique properties has been predicted as the future‐generation metal‐free photocatalyst, electrocatalyst, catalyst support, and a host to chelate with metal ions . A wide variety of low‐cost high nitrogen‐containing organic molecular precursors such as guanidine, cyanamide, melamine, urea, dicyandiamide (DCDA), ammonium thiocyanate, and thiourea, can be employed for synthesizing various forms of g‐C 3 N 4 . A perfect semiconducting bandgap accompanied by suitable band edges constitute as ideal parameters of g‐C 3 N 4 that account for its use in various applications such as photocatalytic pathway for the production of H 2 from water through hydrogen evolution reaction (HER), photoreduction of CO 2 into value‐added high energy fuels, clean water production via degradation of organic pollutants, and catalysis in organic synthesis for the production of fine chemicals (Figure B,C) …”
Section: The Evolution Of Carbon Nitridesmentioning
confidence: 99%
“…In addition, this wonder material with unique properties has been predicted as the future‐generation metal‐free photocatalyst, electrocatalyst, catalyst support, and a host to chelate with metal ions . A wide variety of low‐cost high nitrogen‐containing organic molecular precursors such as guanidine, cyanamide, melamine, urea, dicyandiamide (DCDA), ammonium thiocyanate, and thiourea, can be employed for synthesizing various forms of g‐C 3 N 4 . A perfect semiconducting bandgap accompanied by suitable band edges constitute as ideal parameters of g‐C 3 N 4 that account for its use in various applications such as photocatalytic pathway for the production of H 2 from water through hydrogen evolution reaction (HER), photoreduction of CO 2 into value‐added high energy fuels, clean water production via degradation of organic pollutants, and catalysis in organic synthesis for the production of fine chemicals (Figure B,C) …”
Section: The Evolution Of Carbon Nitridesmentioning
confidence: 99%
“…This material with an approximate composition close to C 6 N 9 H 3 that, however, shows some variability, exhibits electronic properties that make it a promising candidate as a photocatalyst for various applications, such as pollutant degradation for wastewater purification, bacterial disinfection, CO 2 reduction for photochemical fuel generation and most prominently H 2 generation via photocatalytic water splitting , . The means to optimize PCN for these purposes include nanostructuring, metal and non‐metal doping and formation of heterojunctions and composite materials of various kinds . While the number of different approaches is large, the basic material almost always stays the same.…”
Section: Introductionmentioning
confidence: 99%
“…[4,5] The means to optimize PCN for these purposes include nanostructuring, metal and nonmetal doping and formation of heterojunctions and composite materials of various kinds. [6][7][8][9] While the number of different approaches is large, the basic material almost always stays the same. Other carbon nitride materials, that exhibit very similar properties, are often overlooked due to a more complex synthesis process or simply because they are less known.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that by doping small amounts of certain heteroatoms on the surface of carbon nitride, yield of photocatalytic activity was increased . The bare graphitic carbon nitride has a low efficiency compared to the doped one because of better light absorption as well as photocatalytic activities .…”
Section: Introductionmentioning
confidence: 99%